Hubungan Ketuban Pecah Dini dengan Kejadian Sepsis Neonatorum Pada Bayi di Rs Robert Wolter Mongisidi TK. Iikota Manado - Andini Fares; Ike Fitrah Atul Chabibah; Desiska Pricillia Tumatar (Jurnal Ners, 2026)
Premature rupture of membranes is a common pregnancy complication that impacts fetal and maternal outcomes. The purpose of this study was to examine the relationship between premature rupture of membranes and the incidence of neonatal sepsis in infants at Robert Wolter Mongisidi Hospital, Level II, Manado City. The population in this study was 32 infants. The study was conducted from June 20-26, 2025. This study used a retrospective method with a cross-sectional approach. This research was conducted at the Robert Wolter Mongisidi Hospital, Level II, Manado City. The sampling technique used total sampling. The sample collection used observation sheets, and the data were then processed using the Chi-square statistical test with a significance level of p = (α< 0.000). The results of the Chi-square statistical test with a significance level of p = (α< 0.000). This means there is a relationship between premature rupture of membranes and the incidence of neonatal sepsis in infants at the Robert Wolter Mongisidi Hospital, Level II, Manado City. The influence of knowledge on adolescent girls' attitudes towards managing dysmenorrhea at MTs Assalam Manado. The conclusion of this study is that there is a relationship between premature rupture of membranes and the incidence of neonatal sepsis in infants at the Robert Wolter Mongisidi Hospital, Level II, Manado City. Recommendations: The results of this study serve as basic knowledge for students and for future developments in the field of obstetrics